Financial contagion within the interbank network - Christina D. Mikropoulou; Angelos T. Vouldis (European Central Bank (ECB), 2023)
The analysis of contagion in financial networks has primarily focused on transmission channels operating through direct linkages. This paper develops a model of financial contagion in the interbank market featuring both direct and indirect transmission mechanisms. The model is used to analyse how shocks originating from outside sectors impact the functioning of the interbank market and investigates the emergence of instability in this setting. We conduct simulations on actual interbank bilateral exposures, constructed manually from a supervisory dataset reported by the largest euro area banks. We find that while the impact of direct contagion increases gradually with the shock intensity, the effect of indirect contagion is subject to threshold effects and can increase abruptly when the threshold is exceeded. In addition, the risk posed by indirect contagion has a higher upper bound compared to direct contagion. Finally, we find that in terms of overall impact, the shocks to the value of sovereign debt and non-bank financial institutions represent the most significant risk to the functioning of the interbank market.
Keywords: G01; G21; G23; D85; 330; Banking sector; Funding concentration risk; Contagion; Network analysis